Fear in Beauty: Sylvia Plath’s Reflections in Mirror - Adhikari, Bhawani Shankar (Damak Campus Journal, 2024)
This research aims to explore the role of fear and its outcome in the quest for beauty in Sylvia Plath’s poem “Mirror”. Beauty has been defined as the source of power as well as the cause of the annihilation of the entire civilization. Internal beauty has a superior role to external beauty. The persona of the poem has been found engaged in the quest for external beauty even in her old age which is unnatural and worthless. Extreme fear has acted negatively and devastatingly to ruin the life of the persona of the poem. It has led the speaker of the poem hopelessness of life and depersonalized condition which compelled her to commit suicide. The role of fear must be focused on the balance form of fear to maintain and achieve the goal in life. Otherwise, fear’s role and its effect tend to be detrimental and destructive to reaching the destination of keeping beauty, peace, and harmony in life. It has been analyzed how fear has acted and affected the life of Sylvia Plath due to extreme fear in beauty’s quest in old age.The original lines of the poem have been adopted as the primary data and analyzed with the support of secondary articles and journals produced on the poem. The speaker’s fear in the poem “Mirror” has been explored in various forms and such fears have been found to be acting actively in the psyche of the speaker in losing her charming facial appearance of her own youth.